Working memory and fluid intelligence: the role executive processes, age and school type in children - Burges Sbicigo, Juliana; Universidade Federal do Rio Grande do Sul (2014)
The aim of this study was to verify which components of the working memory (WM) model (phonological, visuospatial and central executive) predict the performance in fluid intelligence (FI), considering age, schooling and school type. The participants were 419 children aged between six and 12 years old, from the first year to the sixth grade of Primary School from public and private schools of Rio Grande do Sul, Brazil. The WM subtests of the NEUPSILIN-Inf – Brazilian Brief Neuropsychological Assessment Battery – for children – were administered, and Raven’s Colored Progressive Matrices Test served as FI measure. In the linear regression analysis, the executive component primarily explained the relationship between WM and FI in children, rather than phonological component. When sociodemographic variables were included, age, school type and the executive component explained 47% of FI variance, but the predictive power of the executive component was reduced. The results reinforce the primary relationship between executive processing of WM and FI, as well as the importance of taking into account sociodemographic variables, so the relationship between these constructs are not overestimated.